Menumbuhkan Jiwa Entrepreneur Mahasiswa melalui Pelatihan Kreativitas dan Inovasi: Developing Students' Entrepreneurial Spirit through Creativity and Innovation Training - Galib, Mukhtar; Maulana, Maulana; Basri, Muhammad; Mashuri, Arif; Ardasanti, Andi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Creativity and Innovation Training to Foster Entrepreneurial Spirit among Students aims to enhance students' knowledge, skills, and confidence in entrepreneurship. The training methods employed include lectures, group discussions, brainstorming, simulations, case studies, workshops, and individual mentoring. Training materials cover entrepreneurship concepts, business opportunities, entrepreneurial characteristics, brainstorming techniques, business model canvas, business plan components, marketing strategies, financial analysis, motivation, self-leadership, and time management. The training outcomes indicate an average increase in entrepreneurship knowledge test scores from 60 to 85. 25 students were able to develop complete business model canvases, and 22 students created comprehensive business plans. Participants also demonstrated improved abilities in generating creative and innovative business ideas, as well as increased confidence levels in initiating and developing businesses. This training shows positive results and can serve as a model for other entrepreneurship training programs to assist students in achieving their career goals as entrepreneurs.